Totally stumped. Tried it several different ways. Can not find a way to solve for x, and I know I am just missing something.

3logbase2(x-1) + log base2 4 = 5 2log base2(x-1) +logbase2(x-1) + log base2 4 = 5 by loga + logb = log(a*b) 2 logbase2 (x-1) + logbse2 (x-1)*4 =5 logbase2 (x-1)^3 *4 = 5 (x-1)^3 = 2^3 x-1 = 2 x = 3

please best my answer

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up